BP neural network based Doppler frequency offset estimation method for 5G high-speed mobile system - Zenghao WANG; Lihua YANG; Lu CHENG; Jie ZHANG; Yan LIANG (Dianxin kexue)
A BP neural network based Doppler frequency offset estimation method was proposed.The proposed method was mainly divided into two stages:offline training and online estimation.Firstly,the training samples were constructed by using random Doppler frequency offset and received pilot signals,and then the training samples were used to train the BP neural network offline,which could complete the mapping relationship between input and output data.Then,based on the trained network,the received pilot signal was used to estimate the Doppler frequency offset online.Simulation results show that the performance of the proposed method is far superior to the existing method,and it has low computational complexity.